Acceptability of older adults as living kidney donors. Issue 3 (May 2016) - Lam, Ngan N.; Garg, Amit X.
Abstract : Purpose of review: Kidney transplantation from a living kidney donor (LKD) is associated with better long-term survival and quality of life for a patient with end-stage renal disease (ESRD) than dialysis. We reviewed recent literature on the acceptability and outcomes of older adults as LKDs, which may be misunderstood in routine care. Recent findings: Studies report that receiving a kidney from an older LKD is associated with worse recipient and graft survival compared with receiving a kidney from a younger LKD, but similar recipient and graft survival to receiving a kidney from a standard criteria deceased donor. A kidney from a younger vs. older LKD results in better graft survival in younger recipients, whereas the graft survival is similar in older recipients. Compared with healthy matched nondonors, older LKDs have a similar risk of death and cardiovascular disease and the absolute risk of ESRD after 15 years remains less than 1%. The estimated predonation and postdonation lifetime risk of ESRD varies by age, sex and race with lower incidences in individuals who are older, female and white (vs. African-American). Summary: Donor and recipient outcomes from several studies support the acceptability of older adults as LKDs.